SUMBANGAN PEMIKIRAN TENGKU LUCKMAN SINAR DALAM MEMPERTAHANKAN KEBUDAYAAN MELAYU DI SUMATERA UTARA - Surya Aymanda Nababan; Muhammad Adika Nugraha; Muhammad Ricky Hardiyansyah; Pulung Sumantri; Wendi Hati Tafonao (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research aims to find out the thoughts of one of the intellectual figures and cultural activists from North Sumatra, namely: Tengku Lukman Sinar Basarshah II, Malay Historian and Culturalist. These are the two identities attached to Tengku Luckman Sinar, SH, Sultan of Traditional Affairs of the Malay Sultanate of Serdang State who holds the title Tuanku Luckman Sinar Basarshah II, SH These two identities are very clearly visible in his various writings, thoughts and activities. So it is appropriate that a series of achievements and various awards fill the pages of his life story. This research uses qualitative methods. Neuman (2000) wrote that the qualitative research process begins with topic selection. After the topic has been narrowed down, it is continued by examining the topic in scientific books or journals, known as literature or library research. Reading results from scientific books and journals will provide a clearer picture of how the topic was discussed and understood by previous writers or researchers. Contemplating Tuanku Luckman Sinar Basarshah II's thoughts is a reflection on the existence of Malay Culture itself. Going through various activities, including cultural themes, academics (teaching lectures), and writing, is an illustration of the greatness of his thinking. When Tuanku Luckman Sinar Basarshah II rose to become the Traditional Head of the Serdang Sultanate, attention and thought about Malay Arts was still maintained. In fact, his attention to the field of Malay Arts was also developed to a broader level, namely Malay Culture. The traditional institution finally became a forum for Tuanku Luckman to ensure that the existence of Malay culture was maintained. At its peak, Tuanku Luckman Sinar Basarshah II played the role of gatekeeper of Malay culture from foreign cultural invasions that came and went.